The impact of Islamic capital market on Malaysian real economy - Gani Ibrahim Musa; Zakaria Bahari; Azreen Hamiza Abdul Aziz (Penerbit Universiti Kebangsaan Malaysia, 2020)
The primary purpose of the financial sector of an economy is financial intermediation. Financial intermediation activities of channelling funds from surplus to the deficit units in the economy including through capital market affect the economic growth of a country. The role of Islamic capital market in the process of affecting the growth of an economy is another dimension in finance-growth nexus. This study empirically examines the impact of Islamic capital market on Malaysian economy. It employs the ARDL bounds test approach for cointegration. The results revealed that in the long-run, Islamic capital market contributes to the Malaysian economy by way of capital formation and the efficiency of the capital served as channels of transmitting growth. However, in the short run, only Islamic capital market measure of Islamic stock market turnover contributes to the economy with productivity of capital as the only channel of transmitting growth. Moreover, there is evidence of causality between the Islamic capital market turnover and the Malaysian economy. The findings imply that the Islamic capital market effectively channelled and pooled funds to productive investment activities. It further proves the notion that in general, Islamic finance is more inclined towards real sector growth as compared to conventional counterpart due to the emphasis on equity-based financing as opposed to debt-based financing.